Uplift response of circular plates as symmetrical anchor plates in loose sand - Niroumand, Hamed (Techno-Press, Ltd., 2014)
Uplift response of symmetrical circular anchor plates has been evaluated in physical model tests and numerical simulation using Plaxis. The behavior of circular anchor plates during uplift test was studied by experimental data and finite element analyses in loose sand. Validation of the analysis model was also carried out with 50 mm, 75 mm and 100 mm diameter of circular plates in loose sand. Agreement between the uplift responses from the physical model tests and finite element modeling using PLAXIS 2D, based on 100 mm computed maximum displacements was excellent for circular anchor plates. Numerical analysis using circular anchor plates was conducted based on hardening soil model (HSM). The research has showed that the finite element results gives higher than the experimental findings in the loose sand.